Korelasi antara Kedisiplinan Siswa dengan Hasil Belajar Bahasa Indonesia Siswa SMP - Windi Rahayu; Nazirun (UIR Press, 2022)
Every student wants to succeed in every lesson. Therefore, the quality of student learning itself must be improved and with the discipline of students in learning this will certainly make the quality of student learning even better and success in every learning will definitely be achieved. So the problem discussed in this research is how is the relationship between student discipline and learning outcomes of Indonesian language students in class VIII SMP Negeri 14 Pekanbaru. The purpose of this study was to describe, analyze, and conclude the relationship between student discipline and learning outcomes of Indonesian language students in class VIII SMP Negeri 14 Pekanbaru. The theory used is the theory of discipline proposed by Tu'u (2004). The method in this research is the correlation method. The approach used is quantitative research. The data collection technique in this research is using a questionnaire technique. While the data analysis technique used is the SPSS version 24 program technique. The sample in this study was class VIII students of SMP Negeri 14 Pekanbaru, totaling 48 students. So, from the results of this study it can be concluded that there is a relationship between the discipline of class VIII students of SMP Negeri 14 Pekanbaru. The relationship between the two variables is classified as high with a correlation value of r = 0.930. Furthermore, the relationship between the two variables is significant because tcount (17.109) > ttable (2.013), meaning that the hypothesis is accepted, which means that there is a significant relationship between student discipline and learning outcomes of Indonesian language students in class VIII SMP Negeri 14 Pekanbaru.